2000
DOI: 10.1016/s0005-2736(00)00157-7
|View full text |Cite
|
Sign up to set email alerts
|

Rectangular solid domains in ceramide–cholesterol monolayers – 2D crystals

Abstract: Very small rectangular domains were observed by atomic force microscopy in binary monolayers of synthetic ceramides and cholesterol. When the cholesterol content is increased the domains are bigger although the rectangular shape is retained. The almost perfect shape of the domains indicates two-dimensional single ceramide crystals. Lipid domains in monolayers of this particular shape and size have to our knowledge not been reported in the literature previously.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
1

Year Published

2001
2001
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 16 publications
1
14
1
Order By: Relevance
“…Because the height of cholesterol and palmitic acid molecules is relatively similar, it is not clear whether AFM would distinguish domains enriched in one of the two components. Another AFM study showed the formation of small rectangular domains in monolayers prepared from cholesterol and ceramides (Ekelund et al, 2000). These domains were interpreted as ceramides domains surrounded by a cholesterolrich phase.…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…Because the height of cholesterol and palmitic acid molecules is relatively similar, it is not clear whether AFM would distinguish domains enriched in one of the two components. Another AFM study showed the formation of small rectangular domains in monolayers prepared from cholesterol and ceramides (Ekelund et al, 2000). These domains were interpreted as ceramides domains surrounded by a cholesterolrich phase.…”
Section: Resultsmentioning
confidence: 96%
“…This conclusion was inferred from the analysis of the methylene deformation and rocking bands, and it was also concluded from this approach that the domains would include at least 100 molecules and that their composition was at least 90% enriched in palmitic acid or ceramides. Finally, recent experiments in atomic force microscopy (AFM) on Langmuir-Blodgett monolayers formed with SC lipid model mixtures indicate phase separations leading to formation of domains that were proposed to be enriched in ceramides (ten Grotenhuis et al, 1996;Ekelund et al, 2000). Forslind (1994) proposed that the organization of SC lipids can be described by crystalline domains surrounded with disordered grain border regions, forming "the domain mosaic model of the skin barrier."…”
Section: Introductionmentioning
confidence: 99%
“…The phase behavior and monolayer properties of many sphingolipids have been investigated in detail before (4)(5)(6)(29)(30)(31). Ceramide forms solid monolayers that are characterized by an asymmetry in the hydrocarbon chains.…”
Section: Introductionmentioning
confidence: 99%
“…Ten Grotenhuis et al, 1996;SchaVer et al, 1999;Ekelund et al, 2000;Sparr et al, 2001). AFM on deposited monolayer Wlms beneWts from high lateral and vertical resolution (a few Ångströms) and simplicity of sample preparation (no decoration or conducting coating is needed).…”
Section: Introductionmentioning
confidence: 99%